Analisys of the methodology applied by the english teacher of the ninth year of basic education at “San José Obrero” Educational Institution In Esmeraldas city during the school year 2014-2015” - Demera Grijalva, Mabel Cristina (2016)
Tesis previa obtención del título de Licenciado/a en Lingüística Aplicada mención Inglés